2015
DOI: 10.1103/physrevd.92.101501
|View full text |Cite
|
Sign up to set email alerts
|

Hypermagnetic fields and baryon asymmetry from pseudoscalar inflation

Abstract: We show that maximally helical hypermagnetic fields produced during pseudoscalar inflation can generate the observed baryon asymmetry of the universe via the B + L anomaly in the Standard Model. We find that most of the parameter space of pseudoscalar inflation that explains the cosmological data leads to baryon overproduction, hence the models of natural inflation are severely constrained. We also point out a connection between the baryon number and topology of the relic magnetic fields. Both the magnitude an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
137
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(140 citation statements)
references
References 36 publications
3
137
0
Order By: Relevance
“…Previous studies [21,22,27,64,65] have shown that a helical hypermagnetic field in the symmetric phase of the EW plasma sources baryon number, which thereby competes against the washout of baryon number by EW sphalerons [74]. Unlike the earlier work, in Sec.…”
Section: Analytic Equilibrium Solutionmentioning
confidence: 80%
See 2 more Smart Citations
“…Previous studies [21,22,27,64,65] have shown that a helical hypermagnetic field in the symmetric phase of the EW plasma sources baryon number, which thereby competes against the washout of baryon number by EW sphalerons [74]. Unlike the earlier work, in Sec.…”
Section: Analytic Equilibrium Solutionmentioning
confidence: 80%
“…These ideas were formulated into a model of baryogenesis by Bamba [25] where the dynamics of an axion field during inflation leads to the growth of a helical hypermagnetic field with a large correlation length, which is partially converted into baryon number by the SM anomalies at the electroweak phase transition (see also Refs. [26,27]). Other related work has explored the connection between helical magnetic fields in the early Universe and the anomalous violation of chiral charge [28][29][30][31][32] (see also Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the form of the coupling f , this gives rise to different magnetic field power spectra [31,[36][37][38][39][40][41]. Alternative models, in which magnetogenesis is driven by a rolling pseudo-Goldstone boson ϕ through its coupling to the electromagnetic field in the form ϕFF , are also very interesting and much studied [42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most of the scenarios presented for the generation of the seed fields in the early Universe operate either at a phase transition [28][29][30][31][32][33][34] or during the inflation [35][36][37][38][39][40][41]. The inflationary mechanisms have received a lot of attention, since they have the advantage of achieving super-horizon correlations and therefore generate much more coherent magnetic fields in the early Universe.…”
Section: Introductionmentioning
confidence: 99%